Effect of Transcutaneous Electrical Acupoint Stimulation on One-Lung Ventilation-Induced Lung Injury in Patients Undergoing Esophageal Cancer Operation. (8th June 2020) - Zhao, Fangchao; Wang, Zengying; Ye, Chengyuan; Liu, Jianming
Abstract : Objective . To investigate the effect of transcutaneous electrical acupoint stimulation (TEAS) on one-lung ventilation-induced injury in patients undergoing esophageal cancer operation. Methods . The participants ( n = 121) were randomly assigned into TEAS and sham groups. The TEAS group was given transcutaneous electrical stimulation therapy. The acupoints selected were Feishu (BL13), Hegu (L14), and Zusanli (ST36) and were treated 30 minutes before induction of anesthesia; treatment lasts 30 minutes. The sham group was connected to the electrode on the same acupoints, but electronic stimulation was not applied. The levels of oxygenation index (PaO2 /FiO2 ) and alveolar-arterial oxygen tension difference (A-aDO2 ) before one-lung ventilation (T1), 30 minutes after one-lung ventilation (T2), 2 hours after one-lung ventilation (T3), and 1 hour after the operation (T4) and the levels of serum tumor necrosis factor- α (TNF- α ), interleukin-6 (IL-6), and interleukin-10 (IL-10) at T1, T2, T3, and 24 hours after the operation (T5) were taken as the primary endpoints. The incidence of postoperative pulmonary complications, removal time of thoracic drainage tube, and length of hospital stay were taken as the secondary endpoints. Results . Compared with that, in the sham group, the level of PaO2 /FiO2 in the TEAS group was significantly increased at T2, T3, and T4, and the level of A-aDO2 was significantly reduced at T2 and T3 (P < 0.05 ). Besides, compared with that, in the sham group, the level of serum TNF- α at T2, T3, and T5, as well as the level of serum IL-6 at T3 and T5, was significantly reduced, whereas the level of serum IL-10 at T3 was significantly increased (P < 0.05 ). The incidences of pulmonary infection and pleural effusion in the TEAS group were significantly lower than that in the sham group, and the removal time of thoracic drainage tube and the length of hospital stay in the TEAS group were significantly shorter than that in the sham group (P < 0.05 ). Conclusions . TEAS could effectively increase the levels of PaO2 /FiO2 and IL-10, reduce the levels of A-aDO2, TNF- α, and IL-6, and reduce the incidence of pulmonary complications. Moreover, it could also contribute to shorten the removal time of thoracic drainage tube and the length of hospital stay.